Indigenous Rights - Kingi, Pauline (The Treaty is always speaking: Te reo o te tiriti mai rano, 1989)
Keywords: civil Rights; history; human rights; indigenous rights; social life and customs; tiriti o waitangi/treaty of waitangi; waitangi tribunal

Chapter Seventeen: 'As for these blankets, burn them' Māori and Indigeneity - Hokowhitu, Brendan (Huia histories of Māori: ngā Tāhuhu Kōrero, 2012)
"Collection of 17 essays from Māori scholars which cover customary law, ancestral law, the natural world, Māori urban protest, health, politics, and customary language and expression"--Publisher's information.
Keywords: government relations; history; identity; indigenous rights; pan-indigenous movement; social conditions; tikanga | indigenous law; tāngata whenua